Discursos de conselheiras de direito sobre educação e cuidado de crianças pequenas de zero a três anos - Santos, Elizangela André dos (2016)
This thesis described and interpreted speeches by municipal councilors of law of the city São Paulo, on education and care of young children from 0 to 3 years. The focus problematized inequality in terms of offers and conditions of stay in education policy in Brazil. The Child Law Advice and adolescents are joint bodies composed of representatives of civil society and government with voluntary work. Municipal Councils Law of Children and adolescents should play social control and political act in accordance with the child's status and adolescents (ECA). The results indicate that the nursery not yet occupied a place in CMDCA / SP according to the respondents. The purpose of the discussion is to affirm the importance of coordination and demand of social movements in the Child Law Advice and adolescents in an effort to ensure the right to education and care for infants and children up to three years in order to make it difficult for familiaristas and emergency policies to the detriment of the right of children to quality education. Social Studies of Childhood advocate childhood as a social and historical construction, proposing a visibility of children in academic research and data, encouraging reflection and defense unequal access to public policies for infants and children. The theory of ideology developed by John B. Thompson (2011) seeks to analyze how the symbolic forms can be used to establish and maintain relations of domination in modern societies and in certain socio-historical contexts. To perform the interpretation, they were used to Hermenêutica Thompson depth authoring (2011), as well as the content analysis developed by Rosenberg (1981) and Bardina (1977)